SUMOylation in α-Synuclein Homeostasis and Pathology - Savyon, Mor; Engelender, Simone (Frontiers in Aging Neuroscience, 2020)
The accumulation and aggregation of a-synuclein are central to Parkinson’s disease (PD), yet the molecular mechanisms responsible for these events are not fully understood. Post-translational modifications of a-synuclein regulate several of its properties, including degradation, interaction with proteins and membranes, aggregation and toxicity. SUMOylation is a post-translational modification involved in various nuclear and extra-nuclear processes, such as subcellular protein targeting, mitochondrial fission and synaptic plasticity. Protein SUMOylation increases in response to several stressful situations, from viral infections to trauma. In this framework, an increasing amount of evidence has implicated SUMOylation in several neurodegenerative diseases, including PD. This review will discuss recent findings in the role of SUMOylation as a regulator of a-synuclein accumulation, aggregation and toxicity, and its possible implication in neurodegeneration that underlies PD.